An unprecedented protocol for the synthesis of 3-hydroxy-3-phenacyloxindole derivatives with indolin-2-ones and α-substituted ketones. Issue 4 (16th December 2015) - Bai, Mei; You, Yong; Chen, Yong-Zheng; Xiang, Guang-Yan; Xu, Xiao-Ying; Zhang, Xiao-Mei; Yuan, Wei-Cheng
Abstract : A reaction between indolin-2-ones and α-substituted ketones was developed and a wide range of 3-hydroxy-3-phenacyloxindoles were obtained in good yield. Abstract : An unprecedented reaction between indolin-2-ones and α-substituted ketones has been developed. Using this protocol, a wide range of biologically important 3-hydroxy-3-phenacyloxindole derivatives could be obtained in good yield (up to 93%) under mild reaction conditions. A possible mechanism of this reaction was tentatively proposed based on some control experiments and MS spectrometry analysis.